2007
DOI: 10.5194/angeo-25-1929-2007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the in-phase relationship between the Indian and subsequent Australian summer monsoons during the past five decades

Abstract: Abstract. This study examines the decadal changes in the in-phase relationship between Indian summer monsoon and the subsequent Australian summer monsoon using observational data from 1950-2005. The in-phase relationship is the tendency for a strong Indian summer monsoon to be followed by a strong Australian summer monsoon and vice versa. It is found that the in-phase relationship was weak during the late 1950s and early 1960s, strengthened to a maximum in the early 1970s just before the 1976/77 Pacific climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Anomalously high MSLP and anomalous divergence of moisture over the Maritime Continent and Australia (Figure 6d,f) support an eastward shift in convective activity, which even in La Niña conditions has little impact on Australia (Cai et al, 2010). Hence, northern Australia is disconnected from the tropical Pacific ENSO influence (Meehl & Arblaster, 2011) and the ENSO‐AUMR teleconnection is weak (Arblaster et al, 2002), as shown during the most recent (1977–1998) pIPO phase (Suppiah, 2004; Yu & Janiga, 2007; Zhu, 2018).…”
Section: Aumr: Decadal Variability and Trendsmentioning
confidence: 99%
“…Anomalously high MSLP and anomalous divergence of moisture over the Maritime Continent and Australia (Figure 6d,f) support an eastward shift in convective activity, which even in La Niña conditions has little impact on Australia (Cai et al, 2010). Hence, northern Australia is disconnected from the tropical Pacific ENSO influence (Meehl & Arblaster, 2011) and the ENSO‐AUMR teleconnection is weak (Arblaster et al, 2002), as shown during the most recent (1977–1998) pIPO phase (Suppiah, 2004; Yu & Janiga, 2007; Zhu, 2018).…”
Section: Aumr: Decadal Variability and Trendsmentioning
confidence: 99%